Dentigerous cyst associated with third molar retained in the maxillary sinus - Diana Alina Fundora-Moreno; Adrian Abel Rodríguez-Corbo; María Teresa Corbo-Rodríguez (Universidad Médica Pinareña, 2020)
Introduction: dentigerous or follicular cyst develops by accumulation of fluid between the crown of the tooth and the cells of the epithelium of the enamel organ, that is to say, it originates in the epithelium of the dental follicle. It surrounds the dental crown of a normal or supernumerary tooth and put a stop to its eruption, which is related to retained teeth. It represents 17 % of odontogenic cysts.